Perioperative Complications of Transvenous Embolization of Ruptured Intracranial Arteriovenous Malformations - He, Yanyan; Bai, Weixing; Xu, Bin; Kang, Xiaoyu; Xue, Jiangyu; He, Yingkun; Li, Tianxiao (Frontiers in Neurology, 2022)
Purpose To investigate the perioperative complications of transvenous embolization of ruptured intracranial arteriovenous malformations. Materials and Methods A total of 27 patients with ruptured intracranial arteriovenous malformations underwent transvenous embolization were enrolled from November 2016 to May 2020 in our prospective database. Perioperative complications and angiographic characteristics were analyzed retrospectively. Results Complete disappearance of the nidus occured in 22 (88%) of 25 patients with technically feasible AVMs immediately after embolization. Two cases were partially treated by transarterial embolization due to the failure of microcatheter placement into the draining vein. Seven (25.9%, 7/27) patients had perioperative complications, including three cases of intraoperative hemorrhage, three cases of postoperative hemorrhage and one case of ischemic infarction. No significant differences in complication rates between patients with nidus ≥3 cm and <3 cm (P = 0.659), eloquent area and non-eloquent (P = 0.137), deep location and superficial (P = 0.637), deep venous drainage and cortical vein (P = 1.0), the number of venous drainage (P = 0.49), the angle of draining vein entering venous sinus <90° and ≥90° (P = 1.0), aneurysms (P = 0.058) and the time between hemorrhage and TVE (P = 1.0) were found. Three of these patients received ventriculostomy, two of which received lumbar drainage treatments at the same time, and four patients just received conservative management. Good outcomes (mRS ≤ 2) at the 1-month evaluation were achieved in 5 of the patients who had complications, but poor outcome (mRS = 5) at the 1-month evaluation was in 1 patient, and 1 lethal complication occurred. Conclusion The most common complication of AVMs with transvenous endovascular embolization is cerebral hemorrhage. The prevention of complications may improve the efficacy of AVM embolization, but the current quality of evidence is low and limited in guiding policy development and improving the TVE for AVMs. It is, therefore, necessary to develop clinical research programs in this field.